Lymphangiosis carcinomatosa independently affects long-term survival of Non-Small Cell Lung Cancer patients. (June 2021) - Heldwein, Matthias B.; Doerr, Fabian; Schlachtenberger, Georg; Menghesha, Hruy; Kuhn, Elmar W.; Scheel, Andreas H.; Michel, Maximilian; Wahlers, Thorsten; Hekmat, Khosro
Abstract: Objective: The significance of postoperatively diagnosed Lymphangiosis Carcinomatosa (L1) as an independent risk factor for long-term survival in Non-Small Cell Lung Cancer (NSCLC) remains controversial. We analyzed the effect of L1 on postoperative survival in stage I, II and III NSCLC-patients. Methods: We investigated all consecutive patients with NSCLC between January 2012 and December 2019 who underwent an anatomical resection and radical lymphadenectomy at our institute. L1-were compared to L0-patients. All patients received adjuvant chemotherapy in accordance with European guidelines. 3- and 5- year survival rates and median-survival were assessed. To investigate whether L1 is an independent risk factor, we carried out a multivariate cox regression and a pair-match analysis looking at different properties such as TNM. Results: A total of 641 patients (L0: 74%; L1: 26%) were analyzed. Baseline characteristics were comparable between groups. The mean age was 65.3 ± 10.2 years and 64.9 ± 9.4 years in the L0 and L1-groups respectively (p-value = 0.703). 58.5% of L0-patients were male (L1: 62.7%; p-value = 0.351). Overall survival in the L1-group was significantly shorter compared to the L0-group (L1: 42.3 ± 2.8; L0: 67.6 ± 2.1 months; p-value<0.0001). We confirmed this finding in a pair-matched analysis (L0: 73.9 ± 4.7 months; L1: 42.2 ± 4.2; p-value = 0.009). 3- and 5-year survival were significantly shorter for L1-patients (3-year: L0: 65.9%; L1: 35.9%; p-value<0.0001) (5-year: L0: 34.9%; L1: 7.5%; p-value<0.0001). Conclusion: L1 is an independent risk factor for long-term survival of patients with NSCLC. This cohort supports that the L0/L1 status should be included in pathological reports. We suggest to further include L0/L1-status in guideline recommendations for NSCLC patients. Highlights: The significance of postoperatively diagnosed Lymphangiosis Carcinomatosa (L1) in NSCLC remains controversial. We analyzed the effect of L1 on postoperative survival in stage I, II and III NSCLC-patients. NSCLC patients with Lymphangiosis Carcinomatosa show significantly poorer 3- and 5- year survival rates. Lymphangiosis Carcinomatosa in NSCLC is an significant independent risk factor for long-term survival rates.